Systematic literature review: Dampak bentakan terhadap kerusakan otak dan perilaku anak - Silvi Pebrianti Senjawiani, Silvi; Rifda Sa'adatul Laila, Rifda; Purwati, Purwati (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2025)
Shouting is often used as a disciplinary method for children, but it can negatively affect their brain development and behavior. In response, this study aims to identify the impact of shouting and explore preventive strategies to mitigate brain damage and behavioral issues in children. A systematic literature review (SLR) method was employed to answer the research questions in a structured manner, following the PRISMA 2020 guidelines. A total of 100 articles were reviewed using the keywords (1) shouting, (2) shouting at children, and (3) the impact of shouting on the brain and behavior. The literature search was conducted using EndNote X9 and assisted by Harzing’s Publish or Perish (PoP), resulting in 10 relevant articles sourced from the Google Scholar database. Data collection involved literature screening and document analysis, followed by content analysis using a thematic qualitative descriptive approach. The results revealed that shouting may impair children's cognitive development (such as memory and concentration), emotional well-being (increased anxiety, stress, and sadness), and behavior (including aggression, withdrawal, and low self-esteem). As preventive measures, the study highlights the importance of loving parenting, gentle communication, positive learning environments, and early intervention. These findings underscore the necessity of adopting positive parenting and educational approaches to support optimal mental health and brain development in early childhood